2019
DOI: 10.1371/journal.pgen.1008253
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclin A—Myb-MuvB—Aurora B network regulates the choice between mitotic cycles and polyploid endoreplication cycles

Abstract: Endoreplication is a cell cycle variant that entails cell growth and periodic genome duplication without cell division, and results in large, polyploid cells. Cells switch from mitotic cycles to endoreplication cycles during development, and also in response to conditional stimuli during wound healing, regeneration, aging, and cancer. In this study, we use integrated approaches in Drosophila to determine how mitotic cycles are remodeled into endoreplication cycles, and how similar this r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 107 publications
(150 reference statements)
4
22
0
Order By: Relevance
“…It is known that the Lin52 protein is required for the Myb subunit to associate with the core of the MMB transcription factor complex (Andrejka et al 2011; Guiley et al 2015; Guiley et al 2018). This lin-52 phenotype is, therefore, consistent with our previous finding that knockdown of Myb switches wing and other cells to endoreplication (Rotelli et al 2019). Similar to Myb knockdown, it is likely that knockdown of lin-52 impairs the induction of mitotic gene expression by the MMB and promotes a switch to endoreplication cycles that skip mitosis (Rotelli et al 2019).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…It is known that the Lin52 protein is required for the Myb subunit to associate with the core of the MMB transcription factor complex (Andrejka et al 2011; Guiley et al 2015; Guiley et al 2018). This lin-52 phenotype is, therefore, consistent with our previous finding that knockdown of Myb switches wing and other cells to endoreplication (Rotelli et al 2019). Similar to Myb knockdown, it is likely that knockdown of lin-52 impairs the induction of mitotic gene expression by the MMB and promotes a switch to endoreplication cycles that skip mitosis (Rotelli et al 2019).…”
Section: Resultssupporting
confidence: 92%
“…This lin-52 phenotype is, therefore, consistent with our previous finding that knockdown of Myb switches wing and other cells to endoreplication (Rotelli et al 2019). Similar to Myb knockdown, it is likely that knockdown of lin-52 impairs the induction of mitotic gene expression by the MMB and promotes a switch to endoreplication cycles that skip mitosis (Rotelli et al 2019). Knockdown of βNACtes6 or lin-52 also reduced the area of the L3-L4 intervein region in adult wings, suggesting that tissue growth through an increase in cell size did not fully compensate for growth by cell proliferation (Figure 2F, K, Table 2).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Follicle cells undergo three endocycles, resulting in a ploidy of 16C. Previous work has shown that there are distinct changes in genome regulation during the endocycle, including a global decrease in transcription, decrease in E2F1 target gene expression, and acquisition of endocycle-specific ORC binding sites (Maqbool et al 2010;Sher et al 2012;Hua et al 2018;Rotelli et al 2019). Therefore, we hypothesized that follicle cell RT may be influenced by this developmentally regulated cell cycle transition.…”
Section: Cell Lineage Is a Major Driver Of Dna Rtmentioning
confidence: 99%